Analysis of Hotspot Distribution on Land Use Patterns in Rasau Jaya District in 2022 - Fidhi Melia Medhina; Diah Trismi Harjanti (Universitas Lambung Mangkurat, 2023)
Rasau Jaya Sub-District has six villages that experience frequent forest and land fires every year. Forest and land fires are caused by climatic and human factors that have an impact on health, socio-economic locally and globally, as well as damage to land cover vegetation. Forest and land fires can be identified by monitoring hotspots on satellite imagery. This research was conducted to identify the distribution of hotspots on land use patterns in the Kecamatan Rasau Jaya. The method used is quantitative descriptive with overlay analysis method using intersect tools on hotspot maps, land-use, and administrative maps. The distribution of hotspots in the Rasau Jaya District in 2022 is relatively large in the western part of the Rasau Jaya District, namely Pematang Tujuh Village and Bintang Mas Village. The type of land use that has a high potential for forest and land fires is agricultural land with 134 hotspots and 91 land use shrubs. Overall, the villages that have the potential for forest and land fires are Pematang Tujuh Village, Bintang Mas Village, and Rasau Jaya Umum Village.